Editorial - Pathil, Kuncheria (Journal of Dharma, 1987)
As a sign of unity and commitment to peace the leaders of world Religions met at the small Italian town of Assisi on October 27, 1986, for a 'World Day of Prayer for Peace' at the invitation of Pope John Paul II. Referring to the significant role religion and prayer could play in achieving peace the Pope said that "in the great battle for peace humanity, in its very diversity. must draw from its deepest and most vivifying sources where its conscience is formed and upon which isfounded the moral action ofall people." Peace is another name for unity. Is this claim made by religion to be the source of peace and unity credible today? Is religion a unifying force or a divisive force in the world? All the religions, indeed, theoreti- cally and doctrinally teach universal love, peace, harmony human solidarity and unity. But, paradoxically, some of the fiercest battle in the history of the world were waged in the name of religion. The religions have, in fact, divided humankind into different camps erecting walls of separation between them and fostering mutual suspicion, distrust, rivalry; fanaticism, suppression and persecution. Moreover, each religion though one and united at the time of its origin became divided in due course into different denominations and sects, plagued by mutual condemnation and excommuni- cation,This ambivalence or paradoxical character or religion with regard to the unity of human kind is the general topic of this Number. How does and how should a religion promote unity and solidarity within itself among its various denominations and with the other religions? The prophetic religions, like Judaism, Christianity and Islam generally claim to be the final revelation of God and, therefore, the only true, absolute and universal religion. The model of unity frequently envisaged by each one was centred in itself to the exclusion of the other religions which were considered false or incomplete and therefore to be dispensed with. Islam is a typical example of this attitude, where the believers of the other faiths are often considered to be 'atheists'. The contribution relating to Islam in tbis Number discusses the plurality of denominations in Islam, such as the Shias and the Sunnis, and brings out their underlying common Islamic vision. What these rival tradi- tions need today is mutual acceptance based on the notion of complementa- rity and tbis attitude has to be extended in their relationship to the other religions too.